Factors influencing level of disclosure of corporate internet reporting among listed companies in Malaysia / Rasimah Suhaili - Suhaili, Rasimah (2019)
Corporate internet reporting is a platform for the organization to communicate to their stakeholders by using internet as the intermediary. Corporate internet reporting offers several advantages for the organization to reach it audience globally and locally. This study observed the level of disclosure of corporate internet reporting among the listed companies in Malaysia. The study was conducted involving 233 companies listed on the Main Market and ACE Market of Bursa Malaysia as at January 2019. The literature review was concentrated on the overview of corporate internet reporting together with the independent variables namely, firm size, firm performance and ownership structure. This research observed the content analysis of the companies' corporate website and the annual reports for the year ended 2017. The intention was to investigate whether the independent variables play vital roles in influencing the level of corporate internet reporting. Correlation analysis and multiple regressions analysis were used to analyze the data in this study. The result revealed the level of corporate internet reporting disclosure in Malaysia is still very much at the moderate level. In addition, the firm sizes hows positive and significant relationship towards corporate internet reporting. However, the firm performance shows a positive but insignificant relationship. Finally, the ownership structure revealed that there was no relationship towards corporate internet reporting. The findings of this research suggest that the companies should disclose more real time information on the corporate website since it will attract potential investors and build a great image for the company.